TARI PIRING PADANG MAGEK (Sebuah Tinjauan Estetik) - Syahrial Syahrial (Institut Seni Indonesia Surakarta, 2002)
Tan Pinng is a traditional art which can be found in every nagan in Minangkabau. Nagari Padang Magek, in Tanah Datar Regency West Sumatera Province, is a nagan which has and maintains Tan Piring. As a traditional art, Tan Pinng holds certain aesthetic values. The aesthetic values are reflected by unity, complexity, and intensity a series of mevements supported by other aspects like costumes, ivoperties, musics, and the like in their presentation.Â Key word. Aesthetic, unity, complexity, and intensity.